Radioscreens. Radio and cinema in Italy, radio on Italian cinema. (1st December 2008) - Perrotta, Marta
This article examines the relationship between radio and cinema, both from historic and aesthetic points of view. The aim of its first section is to consider the mutual impact of the two media and of their output on the specific terrain of Italian popular culture and media history. The second section outlines a range of approaches to the representation of the radio medium in Italian cinema. In particular, looking at Italian movies from the early stages of sound cinema in Italy to the present-day developments of national film production, the article aims to sketch a framework of possible uses of radio sounds, radio tales, radio programmes and stars within the cinema discourses and narrations.